Psychometric properties of the Participation Reasons Scale (PRS ) questionnaire - Kaleta, Agnieszka; Mróz, Justyna; Olczyk, Monika; Kozieł, Dorota (Nursing Problems / Problemy Pielęgniarstwa, 2025)
Providing the public with health services of the highest possible quality requires highly qualified medical professionals who must continue to improve their competencies. Adult learning is influenced by a variety of motivational factors. Adults are more inclined to learn if the process allows them to address existing problems or to provide them benefits from the learning experience. Consequently, fulfilling intrinsic needs serves as a significantly stronger motivating factor than extrinsic rewards, although the latter also holds motivational importance. Adult motivation is shaped by various elements, including success, willpower, values, and enjoyment. In Poland, there are numerous psychological tools available for studying adult motivation; however, there is a notable lack of questionnaires that accurately reflect the specific motivating factors influencing healthcare professionals to engage in lifelong professional education. The implementation of a standardised research tool will enable us to better understand the factors that motivate self-education among professional nurses and how these factors influence the effectiveness of the education and development process throughout their careers. The aim of the study was to adapt the Participation Reasons Scale (PRS) questionnaire (Groteluschen, 1985) linguistically and culturally, and tailor the tool for use in Polish settings. The research involved 564 nurses currently employed in the Świętokrzyskie voivodeship in Poland. The PRS survey was translated into Polish by 2 separate translators and subsequently reviewed for accuracy. The Polish adaptation of the PRS adheres to the fundamental standards regarding the coherence and quality of statement formulation. It meets psychometric criteria for reliability and validity and has demonstrated practical relevance within the nursing profession, serving as a tool to assess the motivational aspects of healthcare workers. Future research could explore the application of this instrument across various geographical regions or among diverse cohorts of healthcare professionals.